Augmented reality-delivered product information at the point of sale: when information controllability backfires - Stefan Hoffmann; Tom Joerß; Robert Mai; Payam Akbar (Journal of the Academy of Marketing Science, 2022)
Augmented reality-delivered product information (ARPI) can overcome the limited space at the point of sale to inform shoppers on demand and will therefore become more widespread in brick-and-mortar stores. To fill the void of academic research, this paper develops a model of how consumers process ARPI and how ARPI can shape brand image and purchase intentions. Making use of the cues-filtered-out theory, this paper suggests that the effect of ARPI controllability depends on information detailedness. An unintended backfire effect of controllability occurs when the accessible information is detailed, which is explained by the mediating process via perceived comprehensiveness. This backfire effect is a risk primarily in busy shopping times. The main experiment conducted in a hypermarket and four follow-up studies (using field, lab, and video settings) empirically confirm the proposed model on the basis of different data sources, including usage tracking, questionnaires, and scanner data. The paper derives managerial implications and outlines directions for future research.
Keywords: 330; Augmented reality; Controllability; Point of sale; Field study; Product information